KONTRIBUSI KEPEMIMPINAN KEPALA MADRASAH DAN IKLIM KERJASAMA TERHADAP MOTIVASI BERPRESTASI GURU MADRASAH ALIYAH NEGERI DI KABUPATEN AGAM - Indra Jaya (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
contribution of leadership and cooperation climate head of madrasah to achievement motivation teachers Madrasah Aliyah Negeri (MAN) in the district Agam. Based on the first observation, the writer found that the motivation to show achievement for Islamic school teacher was low enough, especially in preparing and developing types of creativity/innovation of teaching stuffs. This result is related to the leadership of Islamic school headmaster and cooperation condition. This research is aimed to show about how big is the impact of leadership style of Islamic school headmaster and cooperation condition toward motivation to make achievement for Islamic school teachers.The results showed that: (1) The Teachers’ Competence contributed 62,3% toward the motivation of making achievement for teachers; (2) The cooperation situation contributed 16,1% toward the motivation of making achievement for teachers, and (3) The leadership style of Islamic school headmaster contributed 78,4% toward the motivation of making achievement for teachers in Aliyah State School (MAN) in Agam Regency.Kata Kunci: kepemimpinan, kerjasama, motivasi